2015
DOI: 10.3389/fimmu.2015.00439
|View full text |Cite
|
Sign up to set email alerts
|

MF59- and Al(OH)3-Adjuvanted Staphylococcus aureus (4C-Staph) Vaccines Induce Sustained Protective Humoral and Cellular Immune Responses, with a Critical Role for Effector CD4 T Cells at Low Antibody Titers

Abstract: Staphylococcus aureus (S. aureus) is an important opportunistic pathogen that may cause invasive life-threatening infections, like sepsis and pneumonia. Due to the increasing antibiotic resistance, the development of an effective vaccine against S. aureus is needed. Although a correlate of protection against staphylococcal diseases is not yet established, several findings suggest that both antibodies and CD4 T cells might contribute to optimal immunity. In this study, we show that adjuvanting a multivalent vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…We have recently described a multi-protein vaccine formulation, 4C-Staph, which protects mice from S. aureus infection in different models212223. Since arthrosynovitis and OM are among the most severe S. aureus -dependent diseases in humans345, we wanted to test the efficacy of the vaccine formulation in a mouse model of knee joint infection and evaluate local and systemic host immune responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described a multi-protein vaccine formulation, 4C-Staph, which protects mice from S. aureus infection in different models212223. Since arthrosynovitis and OM are among the most severe S. aureus -dependent diseases in humans345, we wanted to test the efficacy of the vaccine formulation in a mouse model of knee joint infection and evaluate local and systemic host immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that an adjuvanted protein combination vaccine, 4C-Staph, conferred significant protection against different S. aureus strains in multiple murine infection models, and that protection was dependent on both humoral and cellular immune responses21222324.…”
mentioning
confidence: 99%
“…MF59 was shown to create an immunocompetent microenvironment at the injection site by inducing chemokines and cytokines as well as recruiting neutrophils, eosinophils, and, later, DCs and macrophages (7). Previous studies on MF59 suggest that an immunocompetent microenvironment with activated innate immune cells and APCs leads to the induction of effector CD4 ϩ T cells, eventually helping B cells to differentiate IgG antibody-secreting plasma cells (17,(33)(34)(35). By using microarray and immunofluorescence analyses, MF59 was determined to be a strong inducer of cytokines, cytokine receptors, adhesion molecules, and antigen-presenting genes FIG 6 MF59 induces acute production of cytokines and chemokines at higher levels than does alum.…”
Section: Discussionmentioning
confidence: 99%
“…However, a correlate of protection against S. aureus infections is not clearly established, and recent vaccine studies have investigated other S. aureus antigens -e.g. the multi-antigen 4C-Staph vaccine (141).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to manage and prevent infections (e.g. multiple hygiene and decolonisation measures) may be attempted in individuals, small communities or in low incidence settings but are problematic on the larger scale (93,95) and efforts to develop successful vaccines continue (141).…”
Section: Mrsa (Bymentioning
confidence: 99%